Long-term outcomes of catheter ablation for ventricular arrhythmias in post- myocarditis patients; Insights from a meta-analysis of current datv. (14th October 2021) - Androulakis, E; Briasoulis, A; Falconer, D; Lim, W; Siasos, G; Ahluwalia, N; Graham, A; Papageorgiou, N
Abstract: Background: In the past decade, catheter ablation (CA) has become a rapidly expanding treatment option for ventricular tachycardia (VT), however it is not commonly utilized for patients with post-myocarditis VT. We aimed to systematically review up-to-date evidence regarding feasibility, effectiveness, and safety of CA, with a specific focus on long-term relapse rate and procedural complications. Methods: A structured electronic database search (PubMed, Embase, Cochrane) of the scientific literature was performed for studies describing outcomes at up to 7.3 years after CA. The primary outcome measured was VT recurrence post-ablation. Procedural success was defined as freedom of ventricular arrhythmias (at the end of follow-up after an ablation procedure). The secondary outcome was significant procedural complications which included procedural death, stroke, cardiac tamponade, acute myocardial infarction, major vascular complications, and major bleeding, assessed on a study-by-study basis. Results: A total of 186 patients were included in analysis with most patients (88%) being male. Over the follow up period there was a 18% relapse rate (n=34) (Confidence Interval (CI); 0.12–0.24, I 2 ≈0, p=0.77) with the majority of patients remaining VT free for the duration of follow up. Only one study recorded the percentage of re-do procedures. The overall procedural complication rate was 3.0% (n=7, (CI; 0.01–0.07, I 2 ≈0, p=0.44) and of note, there were no peri-procedural deaths or heart transplant surgeries reported. However, a single study reported a mortality of 10% (n=2) during the follow up period. Conclusions: CA is an effective and durable long-term therapeutic strategy for post myocarditis VT patients with limited relapse rate and very low complication rates based on these non-randomised data. Larger randomised-controlled trials with standardised treatment and long follow-up are required to compare CA versus conventional treatment in the post-acute myocardial phase. Funding Acknowledgement: Type of funding sources: None.